IMPLEMENTASI KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KOTA PALU - Agnan, Agnan (Katalogis, 2015)
This research aims at describing the Implementation of Public Policy at the Secretariat of the Regional Representatives Palu City. The research method used is descriptive qualitative research methods and data collection techniques by observation, interviews, and documentation. With the selection of techniques purposively informant as much as 5 people. The results showed under the Public Disclosure Policy Implementation in the Secretariat of the Regional Representatives Palu City to approach the implementation model of Van Meter and Van Horn showed optimal results yet, with some aspects influenced among others: 1). From the aspect of implementation activity and communication between organizations, has been running .2). Characteristics of aspects executing agency / implementor, is still inadequate. 3). From the aspect of social and political conditions, are sufficient, 4). From the aspect tendency (disposition) executive / implementor, already well.